Synthesis and in vivo stability studies of [18F]-zwitterionic phosphonium aryltrifluoroborate/indomethacin conjugates. Issue 28 (29th February 2016) - Chansaenpak, Kantapat; Wang, Mengzhe; Liu, Shuanglong; Wu, Zhanhong; Yuan, Hong; Conti, Peter S.; Li, Zibo; Gabbaï, François P.
Abstract : Conjugation of ortho -phosphonium phenyltrifluoroborates with indomethacin affords conjugates which have been radiolabeled by 18 F– 19 F isotopic exchange in aqueous solutions and imaged by positron emission tomography in mice. Abstract : With the goal of developing new positron emission tomography (PET) probes for imaging inflammation in cancer tumours, we have conjugated zwitterionic phosphonium aryltrifluoroborates as fluoride captors with indomethacin, a known cyclooxygenase 2 inhibitor. The resulting conjugates have been radiolabeled by 18 F– 19 F isotopic exchange in aqueous solutions. NMR studies combined with in vivo data show that the nature of the phosphonium substituents plays an important role on the stability of the radiotracers.